TINJAUAN ELEMEN ELEMEN CITRA KOTA SEBAGAI PEMBENTUK SERI VISUAL DI KOTA JAYAPURA - Alfini Baharudin (Diponegoro University, 2011)
A town ought to have clarity at its planning structure so that the town can give strong picture and image to its public. For the purpose required by existence of town planning structure which covers its functions and visual aspect which be each other related to give clarity. Structural of the town planning among others can be observed visually by through an observation in doing movement of one point to point of others in town. In this study, observation performed at town planning structure of Jayapura by doing observation to structural elements of town planning which there have. Observation there performed visually alongside main road which connects downtown of Jayapura-Abepura-Waena. From result show that town planning structure of Jayapura has one regulating elements in the form of kurvalinier main road which connects downtown of Jayapura-Abepura-Waena. Some of the structural elements of town planning which there have can give picture of strong image, but some elements between it needs arrangement in hope that can give optimal clarity. Result of this study recommends arrangement concept of serial vision at town planning structure of Jayapura according to its hierarchy.